Transparency and trust in the European pharmaceutical sector: outcomes from an experimental study. Issue 9 (20th October 2016) - Löfstedt, Ragnar; Way, Dominic
Abstract : Many European pharmaceutical regulators have committed to a more open, inclusive, and transparent model of regulatory decision-making in recent years. Yet, based on little empirical evidence, they have overwhelmingly adopted 'fishbowl' transparency measures, 'the full disclosure of information without explanatory information or contextualization' (e.g. heightening access to raw data). This paper conveys recent findings from an open-ended questionnaire with 200 face-to-face interviews carried out in the UK and the Netherlands. The study provides evidence on how members of the public are likely to react to 'fishbowl' transparency policies and receiving decontextualized data. After showing respondents raw data from a periodic safety update report that regulators are proposing to proactively release, the survey found they were shocked, concerned, and more worried, while many said they would reconsider taking their medicines and seek further advice. Based on these findings, the authors argue that enhancing 'transparency' needs to be integrated with effective, evidence- and science-based benefit/risk communication.